56.9k views
4 votes
Find the sum of the first 40 terms of the arithmetic sequence-3,1,5,...

User X Squared
by
5.4k points

2 Answers

3 votes


\bf -3~~,~~\stackrel{-3+4}{1}~~,~~\stackrel{1+4}{5}~~,~~...\qquad \qquad \stackrel{\textit{common difference}}{d = 4} \\\\\\ n^(th)\textit{ term of an arithmetic sequence} \\\\ a_n=a_1+(n-1)d\qquad \begin{cases} a_n=n^(th)\ term\\ n=\textit{term position}\\ a_1=\textit{first term}\\ d=\textit{common difference}\\[-0.5em] \hrulefill\\ a_1=-3\\ d= 4\\ n= 40 \end{cases} \\\\\\ a_(40)=-3+(40-1)4\implies a_(40)=-3+(39)4\implies a_(40)=153 \\\\[-0.35em] ~\dotfill


\bf \textit{sum of a finite arithmetic sequence} \\\\ S_n=\cfrac{n(a_1+a_n)}{2}\qquad \begin{cases} a_n=n^(th)\ term\\ n=\textit{last term's}\\ \qquad position\\ a_1=\textit{first term}\\[-0.5em] \hrulefill\\ n = 40\\ a_(40)=153\\ a_1=-3 \end{cases}\implies S_(40)=\cfrac{40(-3+153)}{2} \\\\\\ S_(40)=20(150)\implies S_(40)=3000

User Saragis
by
5.7k points
5 votes

Answer:

Sum of Arithmetic Sequence


S_(n) = (a-l) or
S_(n) = (1)/(2) n(2a + (n-1)d)

Where:

  • a = first term
  • l = last term
  • d = common difference
  • n = number of terms

a = -3

l is unknown

d = 1 - -3 = 4

n = 40

Use the second equation because l in unknown.


S_(40) = (1)/(2)40(2(-3) + (40-1)4)


S_(40) = (1)/(2)40(-6 + (39)4)\\S_(40) = (1)/(2)40(-6 + 156)\\S_(40) = (1)/(2)40(150)\\S_(40) = (1)/(2)6000\\S_(40) = 3000

User Krishnaraj
by
5.5k points